Analisis Kemampuan Menulis Teks Eksplanasi Peserta Didik Kelas V Sekolah Dasar - Anggun Floresita Ramadani; Sovi Helena Safitri; Chandra Chandra; Tiok Wijanarko (BADAN PENERBIT STIEPARI PRESS, 2024)
There is explanatory writing material in class V of elementary school, which prompted this research. Writing explanatory texts based on ideas from experience, imagination, or ideas is a learning objective in Class V. The aim of this research is to provide an overview of explanatory text writing written by students in class V at Bandar Buat Elementary School. The writing is then analyzed using an assessment rubric based on the student's writing assignment sheet. The suitability of the content of the text to the title, accuracy of sentence structure, effectiveness of word/vocabulary choice, effectiveness of sentences, and effectiveness of writing punctuation are some indicators of two aspects of explanatory writing. This research was conducted on three students in class V of Bandar Buat Elementary School. Descriptive analysis and data collection methods were used twice in this research. According to research, only one in three students in class V of Bandar Buat Elementary School has written explanatory text that meets the aspects. Apart from that, only one in three students fulfilled the linguistic aspects in their explanatory text writing.